Analysis of Factors Related to Self-Care In Terminal Renal Failure Patients Those Who Are Taking Hemodialysis - Khosi’in Khosi’in; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
This study aimed to examine factors related to self-care in end-stage renal disease (ESRD) patients undergoing hemodialysis. This study design is a comparative categorical analysis by cross-sectional. Was done to 92 hemodialyses this study was conducted at the hemodialysis unit of Dr. Muhamad Yunus hospital Bengkulul. Data was collected by a self-care measurement scale modified questionnaire. self-care level was 50% desirable. No correlation between age, sex, education level, HD duration, family income, and depression to self-care, there is a correlation between self-efficacy and social support to self-care. Self-efficacy is the most influential factor in self-care, it is important to increase self-efficacy by education program about ERSD and hemodialysis.